2011
DOI: 10.1016/j.jcrs.2011.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and long-term outcomes of toxic anterior segment syndrome at Aravind Eye Hospital

Abstract: Although it is impossible to generalize for all etiologies, this study found that TASS is uncommon but not rare, responded to intensive topical antiinflammatory medication, and was usually associated with a good visual outcome. Anterior capsule contraction and PCO were the principal delayed-onset complications beyond those present 1 month postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 15 publications
0
44
1
2
Order By: Relevance
“…It usually occurs acutely, but delayed onset has been reported as well 1. The incidence is variable with reported rates between 0.22%2 and 0.8%3 in different series. The most common finding is diffuse limbus-to-limbus corneal oedema secondary to damage from the toxic insult to the endothelial cell layer.…”
Section: Introductionmentioning
confidence: 99%
“…It usually occurs acutely, but delayed onset has been reported as well 1. The incidence is variable with reported rates between 0.22%2 and 0.8%3 in different series. The most common finding is diffuse limbus-to-limbus corneal oedema secondary to damage from the toxic insult to the endothelial cell layer.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective case series from Aravind Eye Hospital in India recently reported an incidence of 0.22% (60 eyes from 26 408 cataract surgeries). 1 Patients typically present within 12 to 48 hours postoperatively, and the most common finding is a diffuse limbus-to-limbus corneal edema secondary to damage of the endothelial cell layer. Widespread breakdown of the blood-aqueous barrier is also characteristic, with fibrin formation in the anterior chamber and increased anterior chamber inflammation, often resulting in a hypopyon.…”
Section: Resultsmentioning
confidence: 99%
“…Clinicians should also be wary of the use of pain as a differentiating factor as pain in endophthalmitis is only present in about 75 per cent of patients . Furthermore, despite TASS being known to occur in clusters, Sengupta and colleagues found that 52 per cent of cases were sporadic. There is also often under‐reporting of sporadic cases.…”
Section: Discussionmentioning
confidence: 99%
“…Visual prognosis is usually excellent due to its responsiveness to topical steroids. Sengupta and colleagues found that the mean visual acuity (VA) was 0.11 logMAR (approximately 6/7.5 Snellen acuity) one month after treatment . Classic features of TASS include early (day zero or one post‐operatively), intense, painless anterior segment inflammation without vitreous involvement .…”
Section: Differentiating Toxic Anterior Segment Syndrome Versus Infecmentioning
confidence: 99%